Black Rice Extract Reduces Body Weight, Waist Circumference, Body Mass Index and Lipopolysaccharide in Obese Subjects: A Preliminary Study - Armanto Makmun; Agussalim Bukhari; Nurpudji Astuti Taslim; Aminuddin Aminuddin; Ferry Sandra (Indonesian Biomedical Journal)
BACKGROUND: The prevalence of obesity, or an excessive fat accumulation, is keep increasing. In obesity, inflammation can be induced by leaky gut due to the intestinal tight junction barrier dysfunction. Zonula occludens-1 (ZO-1) plays a role in developing intestinal tight junction barrier dysfunction and gut microbiota imbalance, thus promote the translocation of bacterial endotoxin characterized by lipopolysaccharide (LPS) into circulation. Black rice extract (BRE) has been known to have anti-inflammatory property. This study was conducted to investigate the effect of BRE on body weight (BW), waist circumference (WC), body mass index (BMI), ZO-1 and LPS of obese patients.